L'Architecte est absent : works from the collection of Annick and Anton Herbert : répertoire. - Debbaut, Jan; Fabro, Luciano; Fuchs, Rudi, H.; Gilbert & George; Kounellis, Jannis; LeWitt, Sol; Long, Richard; Merz, Mario; Richter, Gerhard; Toroni, Niele (Eindhoven : Van Abbemuseum Eindhoven, 1984)
Broodthaers, Marcel ; Anselmo, Giovanni ; Dibbets, Jan ; Richter, Gerhard ; Andre, Carl ; Penck, A.R. ; Toroni, Niele ; Nauman, Bruce ; Fabro, Luciano ; LeWitt, Sol ; Weiner, Lawrence ; Kounellis, Jannis ; Gilbert & George ; Graham, Dan ; Buren, Daniel ; Kawara, On ; Kosuth, Joseph ; Long, Richard ; Brouwn, Stanley ; Paolini, Giulio ; Art & Language ; Judd, Donald ; Barry, Robert ; Cadere, Andre ; Merz, Mario
Engels
Italiaans
L'architecte est absent : works from the collection of Annick and Anton Herbert, Van Abbemuseum Eindhoven, 23.11.1984 - 06.01.1985
boek